Habitus Politik dan Jaringan Non-Partai dalam Kontestasi Pilkada Jember 2024: Perspektif Pierre Bourdieu - azriel akbar (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the role of electoral mobilization and political networks in the victory of the Fawait–Djoko pair in the 2024 Jember Regency local election. It departs from the assumption that electoral success is not solely determined by formal political party support, but also by the effectiveness of non-party networks in reaching and mobilizing voters. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, documentation, and media analysis, and were examined using thematic analysis techniques. The findings reveal that the success of the Fawait–Djoko pair was supported by the synergy between political party networks and non-party networks, such as local elites, volunteers, and social communities. These networks played a significant role in expanding the support base, strengthening political communication, and increasing voter participation through adaptive and context-specific mobilization strategies. Furthermore, electoral mobilization practices indicate the presence of patronage relationships that reinforce voter loyalty at the grassroots level. This study highlights that network-based electoral mobilization constitutes a key factor in shaping the outcomes of local political contests in contemporary electoral democracies.